Legislasi hukum positif (fikih) Aceh: tinjauan pergumulan Qanun Hukum Jinayah - Nasrullah Yahya (State Institute of Islamic Studies (IAIN) Salatiga, 2014)
This article aims to describe the background of the struggle that occurs in the design draft of Qanun Law Jinâyat between the camps of scholars and civilian camps. This occurs because the heated debate in the Qanun contains stoning an adulteress muhsan in one of the article contents, so the legislation Qanun Law Jinayat as positive law (fiqh) Aceh impact stagnation after it was enacted. Then discussed and passed back after repeated revisions by the abolition of stoning law provisions. The method used is qualitative-phenomenological research with the historical approach. The results showed that includes stoning an adulteress muhsan Qanun Law Jinayah not contradict the hadith texts, and this has been agreed upon by the scholars. Terms of stoning also does not violate human rights, but including the goal of Personality ‘(maqasid al-Shari’ah) in the determination of the law, which is for the benefit of humans, in order to protect offspring (hifz al-nasl) as fulfillment daruriyyah (primary) of mafsadat. Artikel ini bertujuan untuk mendeskripsikan latar belakang lahirnya pergumulan yang terjadi pada draft rancangan Qanun Hukum Jinayah, yaitu antara kubu ulama dan kubu sipil. Perdebatan hangat ini terjadi karena dalam Qanun ini memuat hukum rajam bagi pezina muhsan dalam salah satu isi pasalnya, sehingga legislasi Qanun Hukum Jinayah sebagai hukum positif (fikih) Aceh berdampak kemandegan setelah disahkan. Kemudian dibahas dan disahkan kembali setelah dilakukan revisi ulang dengan dihapuskannya ketentuan hukum rajam. Metode yang digunakan adalah penelitian kualitatif- fenomenologis, dengan pendekatan sejarah (historical approach). Hasil kajian menunjukkan bahwa memuat hukum rajam bagi pezina muhsan dalam Qanun Hukum Jinayah tidaklah bertentangan dengan nas hadis, dan ini telah disepakati oleh para ulama. Ketentuan hukum rajam juga tidak melanggar Hak Asasi Manusia, melainkan termasuk tujuan syara’ (maqasid al-shari’ah) dalam penetapan hukum, yaitu demi kemaslahatan manusia, dalam rangka melindungi keturunan (hifz al-nasl) sebagai pemenuhan kebutuhan daruriyyah (primer) dari mafsadat.